1997
DOI: 10.1177/00220345970760031201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Food Texture and Sample Thickness on Mandibular Movement and Hardness Assessment during Biting in Man

Abstract: This study was designed to investigate the relationship among jaw movements, physical characteristics of food, and sensory perception of hardness in man. Vertical movements of the mandible were recorded with an infrared tracking device in humans during biting on two test foods, carrot and cheese. Samples of standard length (2 cm) and width (2 cm) were prepared in three different thicknesses (0.5, 1.0, and 1.5 cm). Nine subjects were asked to perform two types of bite with their incisor teeth. In the first, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 31 publications
3
96
0
Order By: Relevance
“…Food consistency strongly affects jaw-closing muscle activity per chewing cycle during food reduction (16,17), and increased food hardness, toughness, or resistance to trituration increases the number of chewing cycles before swallowing (18,19). The bolus volume in one bite was found to have similar effects on chewing behaviors, as most parameters-including the jaw-closing muscle activity (20,21) and duration (19)-increased with bolus volume. Blissett et al reported that changes in the physical properties of boluses, rather than changes in the bolus volume during chewing, had significant effects on tongue movement (22).…”
Section: Effects Of Bolus Conditions On Squeezing Behaviorsmentioning
confidence: 86%
“…Food consistency strongly affects jaw-closing muscle activity per chewing cycle during food reduction (16,17), and increased food hardness, toughness, or resistance to trituration increases the number of chewing cycles before swallowing (18,19). The bolus volume in one bite was found to have similar effects on chewing behaviors, as most parameters-including the jaw-closing muscle activity (20,21) and duration (19)-increased with bolus volume. Blissett et al reported that changes in the physical properties of boluses, rather than changes in the bolus volume during chewing, had significant effects on tongue movement (22).…”
Section: Effects Of Bolus Conditions On Squeezing Behaviorsmentioning
confidence: 86%
“…In consequence, during chewing, muscle activity is found to respond to food texture as early as the first chew (Mioche et al 2003). Several kinetic parameters of a chewing cycle also depend on the food properties such as its shape (Gibbs et al 1981), vertical dimension (Diaz-tay et al 1991Peyron et al 1997) and jaw closing angle (Agrawal et al 2000). These variations in the general shape of the chewing cycle are believed to reflect some aspects of the intra-oral events of tongue activity which enable, with cohesive food such as meat, the placement of new food surfaces onto dental arches from one cycle to another (Fig.…”
Section: Chewing Pattern and Texturementioning
confidence: 99%
“…As a consequence, the test foods used during the meal were not calibrated in form and size across the different foods. However, food size influences the masticatory muscle activity in human mastication [20,21]. This may have influenced the fact that differences in MT and MC were not consistent across food types when comparing the two groups.…”
Section: Discussionmentioning
confidence: 99%